Stardines swim high across the sky : and other poems [book with audioplayer] - Prelutsky, Jack ([Library Ideas, LLC], 2018)
Sixteen extraordinary imagined creatures inhabit the pages of this unique, inspired, humorous picture book ideal for sharing together, and for reading again and again. Jack Prelutsky reinvents many familiar and beloved animals by combining inanimate objects with them (so, for example, a pair of pants and an anteater become a panteater). Carin Berger's illustrations are showstoppers. Her shadow boxes and dioramas utilize vintage type, ephemera, and such elements as ribbon, cards, buttons, and wood and bring the animals to life. Read it aloud, read it together: this is a catalog of effervescent silliness and will undoubtedly inspire young poets and artists alike.